(untitled) (Journal of Comparative Social Work, 2020)
Introduction: despite universal efforts, child marriages still occur worldwide. However, not all child marriage unions last, and little is known about how such marriages end. Most critically, there is little information on what happens to young mothers when child marriage unions dissolve. This paper explores the experiences of adolescent mothers who were in child marriages in the cultural context of central Malawi. Methodology: using qualitative methods, data was collected in two districts in central Malawi. One focus group discussion (FGD) was conducted with key community members (n=14) and three FGD, guided by an unstandardized interview guide, were conducted with adolescent mothers aged 15-22 years (n=15). The FGD with adolescent mothers were conducted in three groups, ranging from three to nine participants per group. In addition to this, a key informant interview was conducted with a community leader who is traditionally recognized as paramount chief (n=1). The data was analysed using a content analysis. The study applied the concept of ‘doing gender’ by West and Zimmerman (1987) in the analysis. Results: what emerged from the data is that adolescent mothers embodied fragmented identities that are changing over time given the influence of life events. Amid different combinations of roles, several identities were observed: mother, wife, young, adolescent, girl, married, unmarried, victim of child marriage, survivor of child marriage, unemployed, employed, re-enrolled student, and school dropout. While these identities changed, gender did not, thus the changing identifications provided displays for ‘doing gender’ under a diverse set of subjectivities. Expressions of power at the micro-level were demonstrated by adolescent mothers through ‘resilience vs. perseverance’. Conclusions: the study highlights that cultural sensitivity and responsiveness by traditional leaders, such as the chief, play a role in the empowering revisions of one’s identity by championing liberating life events through the termination of child marriage or access to girls’ education regardless of resistance.